Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/tse.2018.2876843
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Update of Discrete Event Controllers

Abstract: Discrete event controllers are at the heart of many software systems that require continuous operation. Changing these controllers at runtime to cope with changes in its execution environment or system requirements change is a challenging open problem. In this paper we address the problem of dynamic update of controllers in reactive systems. We present a general approach to specifying correctness criteria for dynamic update and a technique for automatically computing a controller that handles the transition fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…This paper builds on the synthesis of discrete event controllers and in particular the work presented in [8] that uses LTS and FLTL as the input for synthesis. We strongly build on the result presented in [19] where a general technique for updating at runtime a controller. In this paper we adapt and apply this technique in the context of business process reconfiguration for DCR graph specifications.…”
Section: Discussion and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper builds on the synthesis of discrete event controllers and in particular the work presented in [8] that uses LTS and FLTL as the input for synthesis. We strongly build on the result presented in [19] where a general technique for updating at runtime a controller. In this paper we adapt and apply this technique in the context of business process reconfiguration for DCR graph specifications.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Definition 7 (DCU Problem [19]). Let E = (E, G, L c ) be an old specification, E = (E , G , L c ) be a new specification, T be a safety FLTL formula, R ⊆ (S E × S E ) be a mapping relation of states and, stopOldReq and startNewReq are special events denoting the ending of old and start of new requirements, respectively.…”
Section: Definition 4 (Labelled Transition Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing types of safety for DSUIn this study, we have identified 29 types of safety in DSU. Based on the number of primary studies for each type, we list the top six most demonstrated safety types in Table 9.In addition, number of studies have presented other 23 types of safety including con‐freeness safety [6, 73, 95 ], semantics safety [51, 76, 84 ], version consistency safety [64, 115 ], deadlock‐free safety [112, 118 ], stack safety [76 ], reconcile safety [116 ], update positions safety [51 ], domain safety [53 ], change function safety [51 ], compile‐time safety [54 ], composition‐time safety [54 ], data access safety [76 ], deadlock safety [51 ], trace safety [115 ], disjunction safety [64 ], dynamic reconfiguration safety [5 ], memory safety [95 ], patch safety [101 ], Virtual Machine safety [4 ], safe transition state [69 ], safe trace [69 ], safe function redefinition [99 ], and safe reconfiguration point [70 ]. B. Current techniques to define safety for DSUA group of studies have highlighted 19 different types of techniques to define safety for DSU including update points testing [37, 107 ], exhaustive testing [111 ], formal methods [101 ], checking assertion [95 ], program analysis [117 ], stack map checking [4 ], program monitoring [115 ], static safety checks [57 ], dodging unsafe points [46 ], flow‐sensitive updateability analysis [77 ], marking the unsafe points [46 ], systematic testing [37 ], updateability analysis [127 ], update‐specific testing [111 ], interrupts to detect safety [118 ], verification of binary […”
Section: Resultsmentioning
confidence: 99%
“…In addition, number of studies have presented other 23 types of safety including con‐freeness safety [6, 73, 95 ], semantics safety [51, 76, 84 ], version consistency safety [64, 115 ], deadlock‐free safety [112, 118 ], stack safety [76 ], reconcile safety [116 ], update positions safety [51 ], domain safety [53 ], change function safety [51 ], compile‐time safety [54 ], composition‐time safety [54 ], data access safety [76 ], deadlock safety [51 ], trace safety [115 ], disjunction safety [64 ], dynamic reconfiguration safety [5 ], memory safety [95 ], patch safety [101 ], Virtual Machine safety [4 ], safe transition state [69 ], safe trace [69 ], safe function redefinition [99 ], and safe reconfiguration point [70 ].…”
Section: Resultsmentioning
confidence: 99%